Ayurveda for All - Murali Manohar (V&S Publishers, 2012)
Recent years have seen a tremendous progress in the knowledge and practice of traditional Ayurvedic medicine, not only in India, but the worldover. Once treated with disdain, the exciting discoveries being pioneered by leading research scientists are proving that Ayurveda with its emphasis on health as well as disease is probably the world s most holistic health system. As allopathic drugs extract a heavy toll in costs and side-effects, more and more people worldwide are turning to complementary medical systems like Ayurveda, Homeopathy,Reiki,Accupressure and many others. This book focuses on : *Central tenets of Ayurveda and the various benefits of Ayurvedic therapies*Remedies for conditions ranging from a minor stuffy nose to the potentially fatal brain-stroke ...all dealt with in simple, scientific and lucid language in this easy-to-follow self-help guide.